2021
DOI: 10.3389/fsufs.2021.623611
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polyphenols as Modulators of Food Allergies. From Chemistry to Biological Implications

Abstract: The multifactorial process of aging predisposes humans to infections and inflammatory disorders, thus affecting their quality of life and longevity. Given this reality, the need to increase the consumption of bioactive compounds, like dietary polyphenols emerges in our daily basis mostly due to their health related effects in slowing-down the incidence of chronic and degenerative diseases and even food allergy, which has been growing rapidly in prevalence currently affecting 5% of adults and 8% of children. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 167 publications
(241 reference statements)
1
11
0
Order By: Relevance
“…During peeling, crushing, or squeezing of fruits, p-and o-dihydroxybenzene derivatives are oxidized to quinones, forming soluble and insoluble protein−phenolic complexes with Mal d 1, thereby reducing the allergenicity of allergenic proteins. 74,75 The mechanisms by which phenolic compounds in food matrices affect allergies are complex, and three broad conclusions have been reached; 76 first, binding to allergenic proteins as mentioned above, second, acting as an anti-inflammatory and antioxidant compound acting as a protective agent, 77 and third, through the ability to modulate cellular functions, inhibiting costimulatory molecule expression and cytokine production or increasing their expression on Treg cells. 78,79 4.1.5.…”
Section: Effect Of Food Matrix Interactions On Food Allergiesmentioning
confidence: 99%
See 1 more Smart Citation
“…During peeling, crushing, or squeezing of fruits, p-and o-dihydroxybenzene derivatives are oxidized to quinones, forming soluble and insoluble protein−phenolic complexes with Mal d 1, thereby reducing the allergenicity of allergenic proteins. 74,75 The mechanisms by which phenolic compounds in food matrices affect allergies are complex, and three broad conclusions have been reached; 76 first, binding to allergenic proteins as mentioned above, second, acting as an anti-inflammatory and antioxidant compound acting as a protective agent, 77 and third, through the ability to modulate cellular functions, inhibiting costimulatory molecule expression and cytokine production or increasing their expression on Treg cells. 78,79 4.1.5.…”
Section: Effect Of Food Matrix Interactions On Food Allergiesmentioning
confidence: 99%
“…An interesting phenomenon is that certain apple varieties with higher total phenolic contents are more tolerable in terms of allergenicity, and in this context, researchers found that the interaction between polyphenols and Mal d 1 plays an important role in reducing the allergenic potential. At the same time, phenolic compounds can change the solubility and digestibility of allergens in the body and affect the uptake of allergens in the gastrointestinal tract. During peeling, crushing, or squeezing of fruits, p- and o- dihydroxybenzene derivatives are oxidized to quinones, forming soluble and insoluble protein–phenolic complexes with Mal d 1, thereby reducing the allergenicity of allergenic proteins. , The mechanisms by which phenolic compounds in food matrices affect allergies are complex, and three broad conclusions have been reached; first, binding to allergenic proteins as mentioned above, second, acting as an anti-inflammatory and antioxidant compound acting as a protective agent, and third, through the ability to modulate cellular functions, inhibiting costimulatory molecule expression and cytokine production or increasing their expression on Treg cells. , …”
Section: Effect Of Food Matrix Interactions On Food Allergiesmentioning
confidence: 99%
“…Polyphenols are chemical compounds widely distributed in plants such as vegetables, fruits, cereals, coffee, tea, and wine [ 67 ]. Dietary polyphenols are a broad group of natural heterogeneous components consisting of phenyl moieties, that are hydroxylated.…”
Section: Effect Of Different Phytochemical Compounds On the Modulatio...mentioning
confidence: 99%
“…Dietary components have gained increasing attention in recent years for their ability to prevent and alleviate allergic responses [ 2 , 3 ]. As the main component in fruits, vegetables, and other edible plant parts, polyphenols and polyphenol-rich foods have been reported to exhibit anti-allergic/-inflammatory properties [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary components have gained increasing attention in recent years for their ability to prevent and alleviate allergic responses [ 2 , 3 ]. As the main component in fruits, vegetables, and other edible plant parts, polyphenols and polyphenol-rich foods have been reported to exhibit anti-allergic/-inflammatory properties [ 2 , 3 ]. Dietary polyphenols, such as curcumin (turmeric) and epigallocatechin gallate (EGCG, green tea), are emerging topics of interest and research, as these compounds exhibit potential benefits for human health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%